Trauma-Informed Medical Education (TIME): Advancing Curricular Content and Educational Context - Brown, Taylor; Berman, Sarah; McDaniel, Katherine; Radford, Caitlin; Mehta, Pooja; Potter, Jennifer; Hirsh, David A (Academic medicine, 2021)
The majority of patients and medical students experience some form of psychological trauma or adversity across their life course. All forms of trauma can be associated with adverse health consequences and can negatively affect learning and professional development. Trauma-informed care (TIC) offers a framework to address and mitigate these consequences and promote safety and health. The Substance Abuse and Mental Health Services Administration describes 6 domains of TIC: safety; trust and transparency; peer support; collaboration and mutuality; empowerment, voice, and choice; and cultural, historic, and gender issues. At present, TIC is not taught routinely in undergraduate medical education (UME)-a crucial educational gap given that UME grounds the development of key perspectives and practices that students use throughout their careers. Further, given the prevalence of preexisting trauma among learners and the likelihood of new traumatic exposures during training, medical schools' processes, practices, and learning environments may risk exacerbating or even causing trauma. To address this educational need and support students and their future patients, the authors propose a trauma-informed medical education (TIME) framework. TIME informs medical schools' curricular content and educational context. In UME, curricular content should address trauma epidemiology, physiology, and effects; trauma-informed clinical skills including sensitive communication and physical exam techniques; and trauma-informed self-care techniques including education on organizational resources, how to elicit supports, and personal self-care practices. A trauma-informed educational context encompasses curricular development, including student-faculty coproduction of educational content; curricular delivery, including faculty development on TIC principles; and learning environment, including trauma-informed educational practices, medical student advising, institutional policies, and recruitment. TIME offers practical strategies to support teaching, learning, educational administration, and professional development and aims to inspire new strategies for effective learner and faculty engagement. TIME aims to foster students' development of competency in TIC and promote student engagement, learning, health, and well-being.